Virus interference on local scale viticulture: the case of Moll variety from Majorca (Spain) (Scientia Agricola, 2013)
In Europe, many autochthonous grapevines (Vitis vinifera L.) are only cultivated at local scale, but play a very important economic role due to their strict relation with terroir and wine tipicity. In this study, it was pursued to evaluate the influence of several factors on performance of Moll, the main autochthonous white variety of Majorca, by means of the database coming from a clonal preselection. The effects of multiple virus infections, vintage and vineyard components were studied by univariate linear models and principal component analysis, starting from measurement of production and must quality parameters of several vines located in 14 vineyards belonging to two appellations during four consecutive years (2001-2004). Absence of multiple virus infections, double cordon system, high clay content and Useful Water Reserve in soils have enhanced vine production without inducing considerable alterations in sugar accumulation in berries and acidity. Moll variety presented great viticultural and oenological potentials. Fertile and deep soils should be preferred in order to maximize production. Also, the use of certified propagation material is strongly recommended. However, further investigations are required to optimize must quality by opportune managements. This study does not provide only essential information to improve Moll cultivation in Majorca, but it also represents a useful example to analyze grapevine varieties that are endemically infected by viruses. In fact, in such situations, it may be supposed an insidious interference by viruses on terroir and wine tipicity.